Spanish defensive measures in the Canary Islands in the context of British plans for the conquest of Macaronesia in 1940–1942 - Krelenko, Denis M. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения, 2024)
This article is devoted to the efforts of Francoist Spain to ensure the defense of the Canary Archipelago in 1940–1942. The obviousness of British plans to conquer Macaronesia forced the Spaniards to take measures to preserve sovereignty over the islands. The goal was achieved in conditions of resource scarcity and the threat of a naval blockade. In this situation, the leadership of the defense resorted to emergency measures. A partial mobilization of people and resources was carried out on the archipelago. The metropolis found reserves of weapons and military equipment, which made it possible to equip the created group. The scarcity of the material base limited the capabilities of the contingent, but its presence made it possible to prevent the primary plans of a potential enemy. The article concludes that the Spanish military preparations, along with the political and operational situation, prevented the planned British expansion against the Iberian archipelagos.